2009
DOI: 10.1007/s00415-009-5156-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-epileptic drugs in patients with gliomas and seizures

Abstract: Although seizures in brain tumor patients are common, the knowledge on optimal anti-seizure therapy in this patient group is limited. An observational study was carried out using a database of all patients from the neuro-oncology service during the period 2000-2005, with data on seizure characteristics, therapy with AEDs, the underlying brain tumor and its treatment. A total of 140 brain tumor patients were studied of whom 23.6% had a low-grade glioma, 53.6% a high-grade glioma, and 22.8% belonged to a mixed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(128 citation statements)
references
References 29 publications
3
114
3
8
Order By: Relevance
“…One researcher reported that there was no remarkable difference in survival between the patients with and without VPA. 25) However, this study was not a randomized control study and has the problem that the ratio of high-grade glioma was not similar between the two groups. Another report demonstrated that VPA was well tolerated in heavily pretreated pediatric patients with high-grade glioma with moderate tumor efficacy.…”
Section: Discussionmentioning
confidence: 92%
“…One researcher reported that there was no remarkable difference in survival between the patients with and without VPA. 25) However, this study was not a randomized control study and has the problem that the ratio of high-grade glioma was not similar between the two groups. Another report demonstrated that VPA was well tolerated in heavily pretreated pediatric patients with high-grade glioma with moderate tumor efficacy.…”
Section: Discussionmentioning
confidence: 92%
“…The correlating median survival times were 17.3 months, 14.4 months, and 14.0 months, respectively. It has been hypothesized that valproic acid enhances antitumor effects of chemoradiation through inhibition of histone deacetylase, inducing autophagy [42,43].…”
Section: Cancer Therapy and Oncology International Journalmentioning
confidence: 99%
“…Van Breemen and colleagues found valproic acid alone and in combination with levetiracetam resulted in a 79.3% and 81.5% seizure response rate, respectively [43]. Considerations for use of valproic acid include thrombocytopenia, drug interactions due to inhibition of CYP2C9, the need for add-on agents for further seizure control in some patients, and therapeutic drug monitoring [40,44].…”
Section: Cancer Therapy and Oncology International Journalmentioning
confidence: 99%
“…Similar results were obtained from the use of valproic acid. It was reported by Van Bremen et al, that 79.3% in 99 glioma patients with secondary epilepsy remained entirely seizure free after treatment with valproic acid [5]. Zonisamide, due to its antioxidant and with a low level of anti-cancer drugs interaction properties, is also associated with tumor-associated seizures [6,7].…”
Section: Introductionmentioning
confidence: 99%